Makna Peran Manusia sebagai Khalifah dan Paradigma Teosentrisme dalam Etika Lingkungan Islam - Kurniawan Dwi Saputra; Septiana Dwiputri Maharani (Fakultas Ushuluddin, Universitas Darussalam Gontor, 2023)
The economic progress obtained by humans brought about negative impact on environment. This is the consequence of the anthropocentric view which legitimizes the exploitation of nature. In Islam, the anthropocentric paradigm can be traced back to the interpretation of the caliph concept. This study intends to interpret the concept of caliph from the Qur’an. The purpose of this study is to observe the interpretation of caliph that is in line with the spirit of environmental preservation. This is a qualitative research and uses literature study as a method. The data collected from written sources. Data verification techniques use source triangulation and data analysis techniques is interactive analysis method. This study found that the concept of caliph is in contrast position to the exploitative attitude towards the environment. From a literal study, the word khalifah means ruler or successor to the generation of people that reflects the value of sustainability. The series of verses on the creation of the caliph (al-Baqarah 30) also carries a message against destructive acts on earth (ifsad). Finally, the context of caliph creation of the caliph is aimed at prospering the earth with a just attitude and in accordance with the law of God. Theocentric paradigm is the foundation of environmental ethics in Islam which is more comprehensive than biocentrism and ecocentrism. This paradigm indeed places humans in a central position in the universe. However, this important role aims to actualize the perfection of of every existence. To do that, humans need to avoid acting ifsad (destruction) in relation to nature.